Fuzzy Multidimensional Assessment Approach of Travel Deprivation in Small Underdeveloped Cities: Case Study of Lhasa, China - Gang Cheng; Simin Jiang; Tao Zhang (Journal of Advanced Transportation)
In small, underdeveloped Chinese cities, the travel needs of economically disadvantaged residents have not been satisfactorily met for a long time, and thus, the problem of travel inequality has become increasingly serious. This study developed and applied a fuzzy multidimensional assessment approach of travel deprivation to assess the travel deprivations that arise because of this travel inequity. The resulting model includes both monetary and nonmonetary indicators, and involves multiple measurement items, dimensions, and related weights. Then, this fuzzy multidimensional assessment approach of travel deprivation is used to measure the travel deprivation in the underdeveloped, small city of Lhasa, China. The results identified both differences and similarities between different parts of the city. Among all measured dimensions, the following four dimensions cause strong travel deprivation: disposable income, travel service quality, travel time, and available transportation. Differences in the travel deprivation were identified between different parts of Lhasa, indicating multidimensional travel deprivation. Furthermore, an early warning analysis on travel deprivation and an assessment of different levels of residents’ travel deprivation in underdeveloped cities are presented. These findings provide an effective evaluation of the current situation of travel inequity in underdeveloped small cities.